The Effect Of Peer Support Group On The Quality Of Life Of Adults With Hypertension - Hidayat, Dian Roslan; Syswianti, Desy; Apriningrum, Nelly (Jurnal Medika Cendikia, 2024)
Hypertension can reduce the quality of life of sufferers due to various complications that affect organs and side effects of antihypertensive drugs . One effort to improve the quality of life of hypertension sufferers is through peer support groups . The purpose of this study was to determine the effect of peer support groups on the quality of life of adults with hypertension at the Wanaraja Health Center, Garut Regency. The study was a quasi-experimental study with a static group comparison design . The population in this study were adults with hypertension at the Wanareja Health Center. The sample in this study was taken by purposive sampling of 40 respondents for each group. Data collection was carried out using the EuroQol 5-dimensional questionnaire (EQ-5D-5L). The data analysis technique used Mann Whitney. The results of the study showed that there was an effect of peer support groups on the quality of life of adults with hypertension. Respondents who received peer support groups had a better quality of life than respondents who did not receive peer support groups